Sosialisasi Minat Pertanian Untuk Mewujudkan Ketahanan Pangan Di SD Negeri Banjarejo, Kecamatan Ngadiluwih, Kabupaten Kediri - Anindita, Devina Cinantya; Sari, Difa Pramudita; Ambarwati, Duwi; Priyanto, Aji (Kadiri University, 2022)
The tropical climate gives Indonesia sunshine all around, which has the potential for agricultural development. In line with the development of time, there has been a change in land use from agricultural land to non-agricultural land. Land use changes occur due to an increase in high population and rapid growth in the economic sector. The impact of land conversion is a decrease in food production which can cause food imports to occur. Land conversion impacts economic changes and the composition of labor requirements. Many young people are not interested in working in the agricultural sector and prefer to work in the service sector. The efforts to invite people back to work in the farming sector by socializing the introduction of the farm industry from an early age. The socialization was carried out at Banjarejo Public Elementary School, Ngadiluwih District, Kediri. The socialization target was elementary school students in grades 4, 5, and 6. The socialization method was direct practice related to eggplant and tomato cultivation. The socialization materials included an introduction to the world of agriculture, the practice of direct planting of eggplant and tomatoes, and socialization on the use of organic and inorganic waste. Banjarejo Public Elementary School students were enthusiastic in practicing eggplant and tomato cultivation.Â Iklim tropis membuat Indonesia mendapatkan sinar matahari sepanjang tahun, hal ini berpotensi baik untuk perkembangan pertanian. Sejalan dengan berkembangnya waktu, terjadi alih fungsi lahan dari lahan pertanian ke non-pertanian. Alih fungsi lahan terjadi karena peningkatan pertumbuhan penduduk yang tinggi serta pertumbuhan sektor ekonomi yang cepat. Dampak alih fungsi lahan adalah menurunnya produksi pangan yang dapat menyebabkan terjadi impor bahan pangan. Alih fungsi lahan berdampak pada perubahan ekonomi dan perubahan komposisi kebutuhan tenaga kerja, banyak masyarakat usia muda tidak tertarik bekerja di sector pertanian dan lebih memilih bekerja di sektor jasa. Upaya untuk mengajak kembali masyarakat bekerja dibidang pertanian dengan cara sosialisasi pengenalan sektor pertanian sejak usia dini. Pelaksanaan sosialisasi dilaksanakan di SD Negeri Banjarejo, Kecamatan Ngadiluwih, Kediri. Target sosialiasasi adalah siswa sekolah dasar kelas 4, 5 dan 6. Metode sosialisasi yang digunakan yaitu praktik secara langsung terkait budidaya tanaman terong dan tomat. Materi sosialisasi meliputi, pengenalan dunia pertanian, praktik penanaman langsung tanaman terong dan tomat serta sosialisasi pemanfaatan sampah organik dan anorganik. Murid-murid SD Negeri Banjarejo sangat antusias saat praktik langsung budidaya tanaman Terong dan Tomat.